The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1177/1468798406069801
|View full text |Cite
|
Sign up to set email alerts
|

Exploring connections between emergent biliteracy and bilingualism

Abstract: This article explores the ways in which young emergent bilingual children begin to develop literacy in two languages, Spanish and English.Three case studies of four-year-old Mexican-background children and their families living in southern Arizona are presented from a qualitative socio-psycholinguistic perspective. The children’s home and classroom interactions were observed and analyzed for patterns of language and literacy in their two languages. The findings show that these emergent bilinguals learn and dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
11

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(113 citation statements)
references
References 22 publications
(26 reference statements)
2
90
0
11
Order By: Relevance
“…Preschool Latino Immigrant Children practices of Latino immigrant children in both the classroom and home contexts (see Reyes, 2006, for more details about the larger project). The preschool, in Southern Arizona, served a lowincome community of predominantly Mexican heritage students.…”
Section: Soltero-gonzálezmentioning
confidence: 99%
“…Preschool Latino Immigrant Children practices of Latino immigrant children in both the classroom and home contexts (see Reyes, 2006, for more details about the larger project). The preschool, in Southern Arizona, served a lowincome community of predominantly Mexican heritage students.…”
Section: Soltero-gonzálezmentioning
confidence: 99%
“…This gave us access to my students' linguistic repertoires and biliteracy became a more natural occurrence in the classroom because students can share their personal experiences that included linguistically diverse events (Manyak, 2002). This project further illustrated Reyes (2006) statement, "when children have access to writing systems and to various literacy activities in both their languages, they are more likely to become biliterate rather than literate only in the dominant language" (p. 289). I hope that teachers will read what I did here and begin to include the many funds of linguistic knowledge that their students have in their classroom pedagogy.…”
Section: Resultsmentioning
confidence: 82%
“…I attempted to "unmark" Spanish in my classroom by adding more Spanish books and dual language books to our classroom library, and sharing comics and photographs with captions in Spanish for morning work. Reyes (2006) claimed that for biliteracy to happen students must have peer and adult support at school and at home. So, I encouraged students to engage with these "new" texts in multiple ways by reading with a partner and taking dual language books home to read with their families.…”
Section: What I Knew About Biliteracymentioning
confidence: 99%
“…Bilingual education teachers, therefore, mediate language and literacy learning opportunities when they "apprentice" learning and enable bilinguals to try out ideas and actions through collaborative social practices (Vygotsky, 1978). In terms of successful biliteracy development, G. Li (2006) and Reyes (2006) found that the home environment was especially influential. Biliteracy facilitates the interpretation of texts when the native language, the second language, and bi/multicultural knowledge are engaged during reading.…”
Section: Research Overviewmentioning
confidence: 96%